Pengaruh Digitalisasi Pajak, Pemahaman Peraturan Pajak Serta Kepercayaan Masyarakat Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Pulogadung Jakarta Timur Tahun 2023 - Wulandari, Winda; Sinaga, Aprilia Nita (Jurnal Ilmu Administrasi Publik, 2024)
Taxpayer compliance is a form of fulfilling taxpayers' obligations to the state. This study was conducted to test the factors that affect the compliance of individual taxpayers at KPP Pratama Pulogadung.The research method was carried out using the multiple linear regression method with a sample of 100 respondents. Based on the results of the study, it is known that tax digitization has an effect on the compliance of individual taxpayers at KPP Pratama Pulogadung, understanding of regulations affects the compliance of individual taxpayers at KPP Pratama Pulogadung, public trust has no effect on the compliance of individual taxpayers at KPP Pratama Pulogadung.